Eleocharis reznicekii (cyperaceae), a new species from the mexican high plateau - González Elizondo, M. Socorro; Rosen, David J.; Carter, Richard; Peterson, Paul M. (Instituto de Ecología, A.C., 2007)
Eleocharis reznicekii (Cyperaceae, subg. Eleocharis, series Eleocharis), is described and illustrated. It is morphologically intermediate between E. densa and two species of Eleocharis subseries Eleocharis (E. macrostachya and E. palustris). The new species differs in a combination of characters including conspicuously compressed culms (3 to over 5 times wider than thick) and stylopodium sessile on a thin annular base. Eleocharis reznicekii differs additionally from E. densa by having relatively lax spikelets, mostly bifid styles, and achenes almost smooth at 30x. From E. macrostachya and E. palustris it is distinguished in its oblong to linear-oblong spikelets, the proximal floral scale clasping only 1/3 to slightly more than 1/2 of the culm, and the proximal plus 1-2(3) subproximal scales without a flower. Eleocharis reznicekii is known only from the state of Durango, in the Mexican high plateau and piedmont of the Sierra Madre Occidental.